The quasi‐ductile resistance of compressed spun concrete beam‐columns - Kliukas, Romualdas; Kudzys, Antanas; Vadlūga, Romualdas (Journal of Civil Engineering and Management, 2010)
The expediency of reinforcing precast spun concrete members of annular cross sections reinforced by high‐strength steel bars is discussed. Test materials, mechanical properties, production and testing procedures of plain and rein‐forced spun concrete specimens are presented. The quasi‐ductile strength and strain features of concentrically and eccentrically loaded specimens are considered. The modelling of a bearing capacity of beam‐columns of annular cross sections is based on the concepts of bending with a concentrical force and compression with a bending moment. The comparison of modelling and test data of spun concrete beam‐columns is analysed. First Published Online: 24 Jun 2011